EVALUATING EFFICACY AND SAFETY OF SUPRACHOROIDAL TRIAMCINOLONE ACETONIDE FOR PATIENTS WITH RETINAL VEIN OCCLUSION - CHAUHAN , K; SAIGOL , HK; AHMAD , NI; ALI , F; AKHTAR , S; RAUF , A (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in the Ophthalmology department, Sir Ganga Ram Hospital, Lahore, from January 2022 to January 2023 to compare the efficacy and safety of intravitreal (IVT) Bevacizumab alone with the suprachoroidal injection of CLS-TA (an injectable form of triamcinolone) along with IVT Bevacizumab in patients with retinal vein occlusion (RVO) induced macular edema in treatment naïve patients. Participants were randomized 1:1 to the IVT Bevacizumab group, and suprachoroidal injection of CLS-TA combined with IVT Bevacizumab group. Participants in both groups were administered drugs and monitored for 30 minutes after the injections. The final evaluation was done after 3 months. Results showed that the Bevacizumab group required 22 re-treatments of the participants for 3 months follow-up, while the combination group required 8 re-treatments (P=0.013). Regarding safety, 1 patient had cataract progression unrelated to the study drug. Combining steroids with vascular endothelial growth factor (VEGF) suppression benefits RVO-induced macular edema. It improves vision, reduces injection frequency, and provides rapid resolution. It is also seen that suprachoroidal delivery of CLS-TA is associated with a reduced risk of increased IOP and cataract progression compared to typical intraocular steroids. Regarding safety, 1 patient had cataract progression unrelated to the study drug. Combining steroids with vascular endothelial growth factor (VEGF) suppression benefits RVO-induced macular edema. It improves vision, reduces injection frequency, and provides rapid resolution. It is also seen that suprachoroidal delivery of CLS-TA is associated with a reduced risk of increased IOP and cataract progression compared to typical intraocular steroids.